Gender Differences in Sabotage: The Role of Uncertainty and Beliefs - Simon Dato; Petra Nieken (Center for Economic Studies and ifo Institute (CESifo), 2018)
We study gender differences in relation to performance and sabotage in competitions. While we find no systematic gender differences in performance in the real effort task, we observe a strong gender gap in sabotage choices in our experiment. This gap is rooted in the uncertainty about the opponent's sabotage: in the absence of information about the opponent's sabotage choice, males expect to suffer from sabotage to a higher degree than females and choose higher sabotage levels themselves. If beliefs are exogenously aligned by implementing sabotage via strategy method, the gender gap in sabotage choices disappears. Moreover, providing a noisy signal about the sabotage level from which subjects might suffer leads to an endogenous alignment of beliefs and eliminates the gender gap in sabotage.
Keywords: J16; M12; C91; 330; gender; sabotage; tournament; belief formation